Isotopic lipid biomarker from the NGaoundaba peat deposit (Tropical Africa) covering the Holocene - Schaaff, Valentine; Grossi, Vincent; Makou, Matthew; Garcin, Yannick; Deschamps, Pierre; Hamelin, Bruno; Kiahtipes, Christopher Albert; Sebag, David; Ngounou Ngatcha, Benjamin; Ménot, Guillemette (PANGAEA, 2025)
This dataset includes lipid biomarker data from a peat sequence (named NGBA19) collected at the NGaoundaba peat deposit in 2019. The NGaoundaba peat deposit is located in North East Cameroon (N 7.135°, E 13.690°, 1175 m a.s.l). The 6-meter core was collected using a Russian peat corer. The core was subsampled at 2.5-cm intervals. Analyses were performed on 73 samples. Measurements were performed between 2020 and 2024 at the LGL-TPE (University Claude Bernard Lyon 1). The NGBA19 core covers the last 10 ka (detail on the datation method and results are given in Schaaff et al. (2023, doi:10.1016/j.orggeochem.2023.104589). This dataset is associated to a publication: Sensitivity to climate and vegetation dynamics of a peatland record from Central Cameroon during the African Humid Period (QSR). The publication details the full method used to obtain the data. The study focus on paleoclimatic and paleoenvironmental reconstructions particularly during and after the African Humid Period. This file contains long-chain n-alkanes carbon and hydrogen isotopic composition. Isotopic compositions are given as δ13C and δD for carbon and hydrogen, respectively. These data were collected using GC-IRMS. Uncertainties were calculated based on duplicate measurements of each sample. When the concentration of the sample did not allow duplicate measurement, the uncertainty corresponds to the mean value of all measured samples. The carbon isotopic compositions are corrected for Suess effect. We provided both uncorrected δD values(δDuncorr) and δD values corrected for vegetation change (δDcorr). Correction methods are presented in detail in the associated article.
Keywords: African Humid Period; alkanes; Biomarker; GDGT; pollen analysis; Tropical peatlands